Percutaneous Dilatational Tracheostomy in Ankylosing Spondylitis (Bechterew Disease) Is Feasible and Not Associated With Higher Complication Rates. (July 2018) - Hamsen, Uwe; Kamp, Oliver; Kaczmarek, Chris; Aach, Mirko; Waydhas, Christian; Schildhauer, Thomas A.; Jansen, Oliver
Background: Ankylosing spondylitis (AS) is a common disease with an incidence of approximately 0.5% in Europe, causing severe limitations of axial spine mobility and cervical kyphosis. Deformities of the cervical spine and the temporomandibular joints could increase the risk of complications while performing an intubation or tracheostomy. The percutaneous dilatational tracheostomy (PDT) is a standard procedure in intensive care medicine. However, the combination of cervical kyphosis and osteoporosis makes patient positioning challenging. Therefore, one could conclude that patients with AS are not candidates for PDT, but neither studies nor case reports yet reported about feasibility of this procedure in AS. Methods: Retrospective analysis at a level 1 trauma center of patient records from 2002 to 2016, assessing all patients with AS and PDT. Results: A total of 31 patients with AS have been subjected to PDT. All PDTs were performed using the modified Ciaglia single-step dilatational technique. Neither cardiopulmonary nor surgical complications occurred during the procedure. One patient received a change of the existing airway prior to the procedure; a small nasal tube was changed for a laryngeal mask. Conclusion: Although head positioning may be challenging, PDT should be taken into consideration for patients with AS. In the hands of an experienced doctor, it is safe and feasible.